Perkembangan Islam pada Masa Dinasti Umayyah - Eggi Martiansyah; Nabila Septiana; Razin Faldam; Hudaidah Hudaidah; Risa Marta Yati (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to examine the development of Islam during the Umayyad Dynasty as one of the important periods in the history of Islamic civilization. The main focus of the discussion is directed at the process of the emergence of Muawiyah ibn Abi Sufyan as the first caliph of the Umayyad Dynasty and his efforts to establish dynastic power after the Islamic Civil War (Fitnah Kubra). The Umayyad Dynasty played a strategic role in the transformation of the Islamic government system from an elective caliphate to a hereditary monarchy, while simultaneously expanding the territory of Islam to various regions. This study uses a literature review method with a historiographic approach, namely examining and analyzing relevant classical and modern historical sources. The results show that during the Umayyad Dynasty, Islam experienced significant developments in the aspects of politics, government administration, military, and culture. However, internal political dynamics, conflicts over the legitimacy of power, and dissatisfaction of certain groups also contributed to weakening the stability of the dynasty. This study also describes the process of decline of the Umayyad Dynasty until its eventual collapse and replacement by the Abbasid Dynasty.